Challenges in Inter-rater Agreement on Lamina Propria Fibrosis in Esophageal Biopsies. (March 2023) - Thaker, Ameet I.; Smith, Jacob; Pathak, Mona; Park, Jason Y.
Background: Mucosal biopsies in eosinophilic esophagitis (EoE) can exhibit lamina propria (LP) fibrosis, which may portend stenotic complications; however, the histologic diagnosis of LP fibrosis is subjective. We sought to assess and improve the consistency of LP fibrosis diagnosis among our pathologist group. Methods: At a large pediatric hospital, 25 esophageal biopsy slides from 19 patients (16 with EoE) exhibiting a wide spectrum of LP area, artifacts, and fibrosis severity were scanned into whole-slide images. Staff pediatric pathologists (n = 8) separate from the authors classified each biopsy by LP adequacy and fibrosis severity 1 month before and after completion of an educational tutorial. Consensus was defined as >70% agreement. Results: At baseline, 16/25 (64%) cases reached consensus for no fibrosis (n = 3), fibrosis (n = 7), or inadequate LP (n = 6); agreement was fair (α = 0.34). Post-tutorial, 13/25 (52%) cases reached consensus for no fibrosis (n = 2), fibrosis (n = 7), or inadequate LP (n = 4); agreement was again fair (α = 0.33). There was moderate agreement in grading of fibrosis severity (α = 0.54). Conclusion: We document only fair-to-moderate agreement in the diagnosis of esophageal LP fibrosis and adequacy in a large pediatric pathologist group despite targeted education, highlighting a challenge in incorporating this feature into EoE research and clinical decision-making.